Single-Particle Extinction and Scattering Method Allows for Detection and Characterization of Aggregates of Aeolian Dust Grains in Ice Cores - Potenza, M. A. C.; Cremonesi, L.; Delmonte, B.; Sanvito, T.; Paroli, B.; Pullia, A.; Baccolo, G.; Maggi, V. (ACS Earth and Space Chemistry, 2017)
Mineral dust aerosol in ice cores is one of the most important proxies for paleoclimate research. Under certain conditions, in the deeper part of ice cores, the pristine paleoclimate signal can be altered by in situ formation of dust aggregates, following the relocation of the impurities. Thus, aggregate detection is a critical indication for post-depositional processes. Clues for the presence of aggregates have been provided by anomalously large dust size distributions, while small aggregates were basically invisible to conventional dust analysis techniques. In this paper, we propose an optical approach to this problem based on the single-particle extinction and scattering (SPES) method, which allows researchers to distinguish between compact and non-compact particles through the analysis of samples populated by isometric particles contained in the core samples. This method can potentially be used during continuous flow analyses of ice cores. It allows for the detection of even the tiniest aggregates, falling within the typical size interval of aeolian mineral aerosol. This approach will potentially provide key evidence for assessing the integrity of paleoclimate records.